Preterm-associated visual impairment and estimates of retinopathy of prematurity at regional and global levels for 2010 - Blencowe, Hannah (Nature Publishing Group, 2013)
BACKGROUND: Retinopathy of prematurity (ROP) is a leading cause of potentially avoidable childhood blindness worldwide. We estimated ROP burden at the global and regional levels to inform screening and treatment programs, research, and data priorities. METHODS: Systematic reviews and meta-analyses were undertaken to estimate the risk of ROP and subsequent visual impairment for surviving preterm babies by level of neonatal care, access to ROP screening, and treatment. A compartmental model was used to estimate ROP cases and numbers of visually impaired survivors. RESULTS: In 2010, an estimated 184,700 (uncertainty range: 169,600–214,500) preterm babies developed any stage of ROP, 20,000 (15,500–27,200) of whom became blind or severely visually impaired from ROP, and a further 12,300 (8,300–18,400) developed mild/moderate visual impairment. Sixty-five percent of those visually impaired from ROP were born in middle-income regions; 6.2% (4.3–8.9%) of all ROP visually impaired infants were born at >32-wk gestation. Visual impairment from other conditions associated with preterm birth will affect larger numbers of survivors. CONCLUSION: Improved care, including oxygen delivery and monitoring, for preterm babies in all facility settings would reduce the number of babies affected with ROP. Improved data tracking and coverage of locally adapted screening/treatment programs are urgently required.